Pengaruh Penyuluhan Kanker Payudara terhadap Pengetahuan dan Sikap Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Kelas X SMA N 1 Pundong - Bellavania, Devina; Rokhanawati, Dewi (LPPM Hang Tuah Pekanbaru, 2024)
Breast cancer is one of the most common cancers in Indonesia. Strategies for tackling breast cancer include health promotion, early detection, and case management. This research aimed to investigate the effect of breast cancer education on the knowledge and attitudes towards breast self-examination (BSE) among 10th-grade female students at SMA N (state senior high school) 1 Pundong. This research employed a quasi-experimental with a pretest-posttest control group design. Subjects were chosen using proportional and simple random sampling, which resulted in a sample size of 110 female students. Data were collected using questionnaires. Data analysis was done using univariate and bivariate analysis. Wilcoxon test analysis resulted in a P value of 0.000 (P<0.05) for the knowledge variable and a P value of 0.000 (P<0.05) for the attitude variable, which indicated an influence of breast cancer education on knowledge and attitudes towards breast self-examination (BSE) among 10th-grade female students at SMA N 1 Pundong. Mann-Whitney test analysis yielded a P value of 0.000 (P<0.05) for the knowledge variable and a P value of 0.000 (P<0.05) for the attitude variable, which indicated differences in knowledge and attitudes between the intervention and control groups among 10th-grade female students at SMA N 1 Pundong. It is hoped that the students will perform BSE regularly.